2022
DOI: 10.1111/cch.13044
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes in a cohort of children with congenital Zika syndrome at 12 and 24 months of age

Abstract: Background Early child development is a critical stage of life that influences social, educational and health outcomes worldwide. A few years after Zika epidemic, families of children born with congenital Zika syndrome (CZS) continue to face uncertainties when it comes to the development of their children. The present study sought to analyse the developmental trajectories of a subset of children born with CZS in the first 24 months of life. Methods Thirty‐five children with CZS were assessed with the Bayley‐II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…In one study, the age-equivalent score at 31.2 months for cognitive, motor, and language domains ranged from 2.15 to 3.02 months [68]. The majority of those with cerebral palsy had spastic quadriplegia and had a Gross Motor Function Classification System level of IV or V (nonambulatory) – 96 and 89%, respectively [65 ▪ ,67 ▪ ]. Similar studies from different regions of Brazil found high rates of severe motor impairments, epilepsy, and impairments in vision, hearing, and swallowing during childhood follow-up [69–71].…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 85%
See 2 more Smart Citations
“…In one study, the age-equivalent score at 31.2 months for cognitive, motor, and language domains ranged from 2.15 to 3.02 months [68]. The majority of those with cerebral palsy had spastic quadriplegia and had a Gross Motor Function Classification System level of IV or V (nonambulatory) – 96 and 89%, respectively [65 ▪ ,67 ▪ ]. Similar studies from different regions of Brazil found high rates of severe motor impairments, epilepsy, and impairments in vision, hearing, and swallowing during childhood follow-up [69–71].…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 85%
“…For children with CZS, the mortality rate ratio up to 3 years of age is 11.3 (10.2–12.4) compared with children without CZS [62 ▪ ]. Several cohort studies of Brazilian infants with antenatal ZIKV exposure have reported that children with confirmed CZS had high rates of seizures (42–85%), cerebral palsy (58–100%), and severe developmental delay on Ages and Stages Questionnaire (ASQ-3) (63%) at 12 months [64,65 ▪ ] and 24 months [65 ▪ ,66,67 ▪ ]. When these infants were assessed with Bayley-III, mean cognitive, communication, and motor scores were between −7 standard deviations (SDs) and −14 SDs at 12 and 24 months [65 ▪ ].…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 The syndrome is characterized by fetal brain malformation and microcephaly associated with other conditions, such as hearing, visual, motor, and intellectual disabilities. 1 , 3 According to epidemiological data from the Brazilian Ministry of Health, the majority of confirmed cases of CZS (around 1,711 live births) were born between 2015 and 2017, mainly in the Northeast region, followed by the Southeast region of the country. 4 , 5 Since then, the number of new cases has gradually declined and is now low.…”
Section: Introductionmentioning
confidence: 99%
“…Normocephalic children born to mothers with ZIKV infection during pregnancy, and with no observable Zika-associated birth defects, may also present later with neurodevelopmental delay or postnatal microcephaly [ 3 ]. Recently, studies in the Americas have reported delayed neuro-motor development of children with congenital Zika infection (CZI) or congenital Zika syndrome (CZS) in the two-to-three-year follow-ups [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%